2022
DOI: 10.1002/chem.202201030
|View full text |Cite
|
Sign up to set email alerts
|

Carboxylate Catalyzed Isomerization of β,γ‐Unsaturated N‐Acetylcysteamine Thioesters**

Abstract: We demonstrate herein the capacity of simple carboxylate salts -tetrametylammonium and tetramethylguanidinium pivalate -to act as catalysts in the isomerization of β,γ-unsaturated thioesters to α,β-unsaturated thioesters. The carboxylate catalysts gave reaction rates comparable to those obtained with DBU, but with fewer side reactions. The reaction exhibits a normal secondary kinetic isotope effect (k 1H /k 1D = 1.065 � 0.026) with a β,γ-deuterated substrate. Computational analysis of the mechanism provides a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…Typically, the reactions have been restricted to simple aryl or alkyl aldehydes, and chromatographic purification has been required for the products. On the basis of our previous work on carboxylate catalysis in the enolization of thioesters with simple carboxylate catalysts such as tetramethylammonium pivalate (TMAP), we hypothesized that the diazoacetate aldol reaction should also be amenable to carboxylate catalysis. A few examples of catalytic systems involving carboxylate catalysts have been published, demonstrating diverse applications in C–C bond formation as well as in proton-transfer reactions .…”
Section: Introductionmentioning
confidence: 99%
“…Typically, the reactions have been restricted to simple aryl or alkyl aldehydes, and chromatographic purification has been required for the products. On the basis of our previous work on carboxylate catalysis in the enolization of thioesters with simple carboxylate catalysts such as tetramethylammonium pivalate (TMAP), we hypothesized that the diazoacetate aldol reaction should also be amenable to carboxylate catalysis. A few examples of catalytic systems involving carboxylate catalysts have been published, demonstrating diverse applications in C–C bond formation as well as in proton-transfer reactions .…”
Section: Introductionmentioning
confidence: 99%
“…8,9 Catalytic deprotonation reactions of alkynes without metals are presumed to be highly challenging, 10 although reactions with aldehydes and ketones (Favorskii reaction) have been realized with strong metal-free bases such as quaternary ammonium hydroxides. 11−13 We have previously shown that metal-free catalytic enoyl isomerization 14 and silylative aldol reactions 15 are possible with simple carboxylate salt catalysts, without the need of metal or strong (and potentially nucleophilic) hydroxide bases. In the aldol reaction, the combination of tetramethylammonium pivalate (TMAP) and the neutral silylating agent N,Obis(trimethylsilyl)acetamide (BSA) was required for rapid turnover rates.…”
mentioning
confidence: 99%
“…We have previously shown that metal-free catalytic enoyl isomerization 14 and silylative aldol reactions 15 are possible with simple carboxylate salt catalysts, without the need of metal or strong (and potentially nucleophilic) hydroxide bases. In the aldol reaction, the combination of tetramethylammonium pivalate (TMAP) and the neutral silylating agent N , O -bis(trimethylsilyl)acetamide (BSA) was required for rapid turnover rates.…”
mentioning
confidence: 99%
“…8,9 Catalytic deprotonation reactions of alkynes without metals are presumed to be highly challenging 10 although reactions with aldehydes and ketones (Favorskii reaction) have been realized with strong metal-free bases such as quaternary ammonium hydroxides. [11][12][13] We have previously shown that metal-free catalytic enoyl isomerization 14 and silylative aldol reactions 15 are possible with simple carboxylate salt catalysts, without the need of metal or strong (and potentially nucleophilic) hydroxide bases. In the aldol reaction, the combination of tetramethylamonia pivalate (TMAP) and neutral silylating agent N,Obis(trimethylsilyl)acetamide (BSA) was required for rapid turnover rates.…”
mentioning
confidence: 99%